Exploration of Lithium Brine Purification Via Simultaneous Extraction of Magnesium and Boron Using Novel Ionic Liquids: A Theoretical and Experimental Molecular Study - Cardenas-Jiron, G (Elsevier B.V., 2025)
The growing global demand for lithium, crucial for lithium-ion batteries in electric vehicles and industrial applications, highlights the need for more efficient extraction methods. Current lithium brine purification processes struggle to separate lithium from magnesium and boron, affecting production efficiency and profitability. This study explores a novel approach for purifying lithium brines by extracting magnesium and boron using ionic liquids. A dual-function ionic liquid extractant was designed and synthesized, and its effectiveness was evaluated to improve lithium brine purity. Theoretical calculations using Density Functional Theory (DFT) and experimental results demonstrate the potential of the proposed ILs highlighting the complexity of extracting both magnesium and boron. Steric hindrance and electrostatic interactions limit the efficiency of the dual extraction process. This research highlights both the potential for developing more sustainable lithium extraction practices and the significant technical challenge of achieving an efficient dual extraction. © 2025 Elsevier B.V.